Inactivation synergy between high energy neutrons and ⁶⁰Co gamma rays - Slabbert, Jacobus Petrus (Division of Radiology, 2018)
The interaction between sublesions produced by neutrons [p(66)/Be and d(16)/Be] and ⁶⁰Co γ-rays was investigated using mammalian cells, meristematic cells and human lymphocytes. The quality of each radiation source was quantified in terms of molecular yield per unit dose absorbed in a ferrous sulphate xylenol orange solution and was found to vary inversely with the mean LET of the radiation field. Inactivation parameters determined for mammalian and meristematic cells were not significantly different following simultaneous or sequential exposures to d(16)/Be neutrons and ⁶⁰Co γ-rays. Synergistic interaction was observed to be most pronounced in a radiation mixture consisting of about one part neutrons and three parts photons and appeared to be optimal at approximately 5 Gy. This phenomenon led to dose enhancement ratios that increase with radioresistance. Multi-target parameters indicated that on a per gray basis, priming doses of p(66)/Be neutrons and ⁶⁰Co γ-rays induce comparative levels of sublethal damage. However, non-parametric analysis of the survival data showed that mammalian cells regard a priming dose of neutrons as somewhat less effective than an iso-effective photon dose. A greater measure of synergy was observed between photons and priming doses of neutrons with less build-up. This is however mainly due to higher levels of biological damage induced with a more potent configuration of secondary charged particles. Interaction factors compared at levels of iso-effect tend to be smaller when the LET of the priming dose was increased. Split-doses of neutrons in the absence of build-up resulted in "negative" repair. The validity of proposed biophysical models was tested using meristematic cells, as the response of these cells show an apparent absence of intertrack damage. Contrary to expectations, synergistic interaction was observed for both growth delay measurements and micronuclear formations. Chromosome aberrations showed synergy between neutron and photon damage in human lymphocytes, as predicted by interaction functi ons. However, the synergistic interaction noted with micronuclear formation in binucleate cells was at variance with predictions based on biophysical models.